Spin-torque-driven MTJs with extended free layer for logic applications. (14th June 2018) - Raymenants, Eline; Vaysset, Adrien; Wan, Danny; Swerts, Johan; Van Beek, Simon; Zografos, Odysseas; Nikonov, Dmitri E; Manipatruni, Sasikanth; Young, Ian A; Mocuta, Dan; Radu, Iuliana P; Heyns, Marc; et al.
Abstract: The development of low-power spintronic computation would open new paths for advanced logic nodes. It could utilize a ferromagnetic free layer shared by multiple magnetic tunnel junctions to cascade spin-coherent information. The basic component of this device would be a magnetic tunnel junction with an extended free layer. Here, we study the magnetization dynamics of such a system. One or multiple intermediate resistance levels are observed during spin-torque-induced magnetization reversal. Micromagnetic modeling suggests that non-uniform magnetic anisotropy introduced by careful pillar-pattering is a plausible cause of this multi-step reversal.